KONSEP LA IKROHA FI AL-DIN DALAM Q.S AL-BAQOROH :256 KAJIAN ANALISIS TAFSIR MAQOSHID: 1. Pembahasan ayat dan terjemah 2. Analysis ke bahasa an 3. Azbabun Nuzul mikro dan makro 4. Pemahaman Tafsir maqoshid 5. Maqoshid lafadz la ikraha fiddin 6. Praktik maqoshid la ikraha fiddin - LATIFAHMULYANI (Jurnal SUARGA: Studi Keberagamaan dan Keberagaman, 2023)
Along with the development of the times, the human mindset is also growing. This also occurs in the perspective of humans in carrying out their beliefs, and some of them lead to acts of anarchy and religious bigotry. This paper attempts to explain the meaning of "Religious Freedom" as contained in Q.S Al-Baqoroh: 256 which will be examined using maqoshid interpretation studies. With the aim that the Muslim community no longer acts anarchically against minorities. Because it does not reflect the teachings of God and his Prophet. With the hope that we can coexist peacefully without oppression and coercion of beliefs. Thus creating an environment of harmony, tolerance and upholding human values. Because every religion must teach goodness in it.